Cost-effectiveness analysis of hepatocellular carcinoma screening by combinations of ultrasound and alpha-fetoprotein among Alaska Native people, 1983–2012. Issue 1 (31st January 2016) - Gounder, Prabhu P.; Bulkow, Lisa R.; Meltzer, Martin I.; Bruce, Michael G.; Hennessy, Thomas W.; Snowball, Mary; Spradling, Philip R.; Adhikari, Bishwa B.; McMahon, Brian J.
Abstract : Background: The American Association for the Study of Liver Diseases (AASLD) recommends semi-annual hepatocellular carcinoma (HCC) screening using ultrasound (US) in persons with chronic hepatitis B (CHB) virus infection at high risk for HCC such as Asian males aged ≥40 years and Asian females aged ≥50 years. Objective: To analyse the cost-effectiveness of 2 HCC screening methods in the Alaska Native (AN) health system: US-alone, or screening by alpha-fetoprotein (AFP) initially and switching to US for subsequent screenings if AFP >10 ng/mL (AFP→US). Design: A spreadsheet-based model was developed for accounting the costs of 2 hypothetical HCC screening methods. We used epidemiologic data from a cohort of 839 AN persons with CHB who were offered HCC screening by AFP/US semi-annually during 1983–2012. We assumed that compared with AFP→US, US-alone identifies 33% more tumours at an early stage (defined as a single tumour ≤5 cm or ≤3 tumours ≤3 cm in diameter). Years of life gained (YLG) attributed to screening was estimated by comparing additional years of survival among persons with early- compared with late-stage tumours. Screening costs were calculated using Medicare reimbursement rates in 2012. Future screening costs and YLG were projected over a 30-year time horizon using a 3% discount rate. Results: The total cost of screening for the cohort by AFP→US would have been approximately 357, 000 (36, 000/early-stage tumour detected) compared to 814, 000 (59, 000/early-stage tumour detected) by US-alone. The AFP→US method would have yielded an additional 27.8 YLG (13, 000/YLG) compared with 38.9 YLG (21, 000/YLG) for US-alone. Screening by US-alone would incur an additional 114, 000 per extra early-tumour detected compared with AFP→US and 41, 000 per extra YLG. Conclusions: Although US-alone HCC screening might have yielded more YLG than AFP→US, the reduced costs of the AFP→US method could expand access to HCC screening in resource constrained settings.